2018
DOI: 10.1038/s41598-017-18680-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of silver nanoparticle toxicity to algae in soil via photosynthetic and flow-cytometric analyses

Abstract: Soil algae, which have received attention for their use in a novel bioassay to evaluate soil toxicity, expand the range of terrestrial test species. However, there is no information regarding the toxicity of nanomaterials to soil algae. Thus, we evaluated the effects of silver nanoparticles (0–50 mg AgNPs/kg dry weight soil) on the soil alga Chlamydomonas reinhardtii after six days, and assessed changes in biomass, photosynthetic activity, cellular morphology, membrane permeability, esterase activity, and oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The effects of AgNPs (0-50 mg AgNPs/kg dry weight soil) on the soil alga Chlamydomonas reinhardtii after a six-day exposure were evaluated. The photosynthetic activity of Chlamydomonas reinhardtii in AgNP-treated soils decreased at 50 mg AgNPs/kg treated soil in comparison to the control [42].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The effects of AgNPs (0-50 mg AgNPs/kg dry weight soil) on the soil alga Chlamydomonas reinhardtii after a six-day exposure were evaluated. The photosynthetic activity of Chlamydomonas reinhardtii in AgNP-treated soils decreased at 50 mg AgNPs/kg treated soil in comparison to the control [42].…”
Section: Discussionmentioning
confidence: 83%
“…In the study of Hazeem et al [41], it was shown that AgNPs affected Chlorella vulgaris viability only at high AgNP concentrations (>100 mg/L). AgNPs inhibited the growth of Chlamydomonas reinhardtii at concentrations of 40 and 50 mg AgNPs/kg soil [42]. The highest toxicity effect on Dunaliella salina biomass was recorded at 1 mg/L of AgNPs at salinities (35,70, and 140 g/L) [43].…”
Section: Discussionmentioning
confidence: 95%
“…This phenomenon usually occurs because of increased cell size or cell deformation (Franqueira et al, 2000;Franklin et al, 2001). However, an alternative explanation for this change in scattering intensity may be the formation of a mucilaginous sheath around the algal cells, as a protective barrier against the IL (Nam et al, 2018). When CIL <50 mg/L, the MFIs increased generally with CIL.…”
Section: Cell Growthmentioning
confidence: 99%
“…Green Algae 6.1.1. Chlamydomonas Reinhardtii Unicellular, green algae have been widely used as sentinel species for ecotoxicological studies both in freshwater and soil ecosystems [43]. Thus, one of the first attempts to establish the potential impact of novel nanopollutans by using transcriptomics approaches was carried out in the model species C. reinhardtii [31].…”
Section: Transcriptomics Studies In Plants To Evaluate Nanoimpactmentioning
confidence: 99%